Information Record Software for the Implementation of Merdeka Belajar Kampus Merdeka (MBKM) (Case Study MBKM Darmajaya) - Aimar, Nizka; Artaye, Ketut (Prosiding International conference on Information Technology and Business (ICITB), 2023)
MBKM was officially launched by the Ministry of Education, Culture, Research, and Technology (Ministry of Education and Culture) in early 2020 to build high-quality and character-driven human resources. The current support system, especially in the MBKM activities at Darmajaya University, is still insufficient. The processing of student data participating in the MBKM program is still carried out manually using Microsoft Excel or separate Google Forms applications, meaning there is no dedicated system in place. This study aims to develop an information system that can support users in providing management information system services for the MBKM program within the Darmajaya Informatics and Business Institute. This research developed using the Extreme Programming (XP) method, namely software development that pursues an object-oriented approach, which consists of several steps including the planning process (planning), the system design process (design), the process of making program coding and the testing process through program testing, so that system development is in accordance with the objectives and needs of users. The result of this research is a software or information system for implementing Merdeka Belajar - Merdeka Campus based on Mobile Web, which developed to support admission, selection, monitoring and reporting activities for management. Users can manage MBKM activities easily starting from activity registration, guidance, and MBKM activity exams through this information system. This MBKM activity information system was successfully built and can help IIB Darmajaya in managing MBKM activities. Users also consider the MBKM activity information system easy to use.Keywords: Darmajaya, MBKM, system, Linear Search AlgorithmÂ Â